Syndecans and Their Synstatins: Targeting an Organizer of Receptor Tyrosine Kinase Signaling at the Cell-Matrix Interface - Rapraeger, Alan C. (Frontiers in Oncology, 2021)
Receptor tyrosine kinases (RTKs) and integrin matrix receptors have well-established roles in tumor cell proliferation, invasion and survival, often functioning in a coordinated fashion at sites of cell-matrix adhesion. Central to this coordination are syndecans, another class of matrix receptor, that organize RTKs and integrins into functional units, relying on docking motifs in the syndecan extracellular domains to capture and localize RTKs (e.g., EGFR, IGF-1R, VEGFR2, HER2) and integrins (e.g., αvβ3, αvβ5, α4β1, α3β1, α6β4) to sites of adhesion. Peptide mimetics of the docking motifs in the syndecans, called “synstatins”, prevent assembly of these receptor complexes, block their signaling activities and are highly effective against tumor cell invasion and survival and angiogenesis. This review describes our current understanding of these four syndecan-coupled mechanisms and their inhibitory synstatins (SSTNIGF1R, SSTNVEGFR2, SSTNVLA-4, SSTNEGFR and SSTNHER2).